Living longer: Years spent in (bad) health? - Dörte Heger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
A rise in life expectancy for older age groups is accompanied by increasing limitations with everyday activities. - Due to medical and technological progress, life expectancy has increased significantly over the past decade. A large share of this increase occurs for people over the age of 50. However, the rate of illness in the population is simultaneously increasing because the average number of people affected by disease in each age group is rising. At the same time, the limiting effect of diseases remains unchanged. New research findings for European countries show that, as a consequence, additional years of life are spent in bad health.
Keywords: 330